2013
DOI: 10.1590/s1677-5538.ibju.2013.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Differencial proteome of clear-cell renal cell carcinoma (ccRCC) tissues

Abstract: Purpose: We attempted to detect, for the first time in a Brazilian cohort, differences in protein expression between clear-cell renal cell carcinoma (ccRCC) and their normal adjacent tissues, aiming to identify biomarkers and/or therapeutic target candidates for this disease. Material and Methods: Twenty-four ccRCC and adjacent normal tissues were collected after surgery and their protein extracts were quantified, pooled and separated by two--dimensional polyacrylamide gel electrophoresis (2DE), followed by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Tumor markers such as CEA, CA125, and CA19-9 may rise slightly in few cases, but there is no specificity. [13] Among 3 cases in our study, only one case (Case 2) showed slightly increased CEA, while the rest tumor markers were all normal in all 3 cases. Therefore, quite a lot of pancreatic metastases from CCRCC are detected during check-ups or routine physical examination.…”
Section: Discussionmentioning
confidence: 67%
“…Tumor markers such as CEA, CA125, and CA19-9 may rise slightly in few cases, but there is no specificity. [13] Among 3 cases in our study, only one case (Case 2) showed slightly increased CEA, while the rest tumor markers were all normal in all 3 cases. Therefore, quite a lot of pancreatic metastases from CCRCC are detected during check-ups or routine physical examination.…”
Section: Discussionmentioning
confidence: 67%
“…В некоторых случаях заболевание протекает бессимптомно. Онкомаркеры, такие как раково-эмбриональный антиген и СА19-9, могут незначительно повышаться, но специфичность отсутствует [15]. В обзоре 236 случаев метастазов ПКР как одиночных, так и множественных, F. Sellner и соавт.…”
Section: Discussionunclassified
“…The individual spots visualized by this methodology are then excised and subjected to mass spectrometry analysis to identify and annotate the protein spots, with differences in protein spot intensity between experimental conditions inferring differential protein abundance and identification of dysregulated proteins. Multiple studies have leveraged this technique to identify differential expressed protein profiles between ccRCC and NAT samples, followed by immunoblotting or immunohistochemical validation in independent samples [ 26 30 ]. Perroud et al [ 26 ], identified 31 proteins that were differentially expressed between ccRCC tumor tissues and NATs derived from four patients, validating the overexpression of HSP27 (HSPB1) and PKM2 via immunoblotting.…”
Section: Tissue Profilingmentioning
confidence: 99%